The first embryo, the origin of cancer and animal phylogeny. IV. The neoplastic basis for the formation of the innate immune system - Cofre, Jaime (Frontiers in Ecology and Evolution, 2024)
The formation of the innate immune system of animals can only be envisioned after the development of the first metazoan embryo. The decisive role of Embryology in understanding the evolution of the immune system has been inexplicably disregarded in the history of science. Some characteristics of our holozoan ancestors, including macrophage-like movement and enteric phagocytosis, were suppressed by the formation of chains of physically attached cells in the context of embryo multicellularity. The formation of the archenteron during morphogenesis of the first embryo resulted in a meta-organism whose survival was dependent on the ability to perform enteric phagocytosis (nutrition on bacteria). By recognizing the neoplastic basis of embryo formation, it is possible to venture a glimpse at its other face, a process that becomes evident when the extracellular matrix and cadherin junctions are destroyed. What ensues is metastasis (in the case of cancer) or an alternative version controlled by cell differentiation (during embryogenesis). In the context of innate immunity, the development of mesogleal cells by epithelial–mesenchymal transition and differentiation into cells specialized in bacterial recognition allowed the newly formed animal to preserve homeostasis, an innovation that has been maintained throughout evolution. In this article, I will share my first reflections on the embryonic origin of innate immunity and its close relationship with cancer. Innate immunity arises naturally during embryogenesis, which explains why the immune system typically does not react against cancer cells. In its essence, the immune system was created from them. Here, I argue that the first embryo can be understood as a benign tumor nourished and protected by the innate immune system.